2014
DOI: 10.1002/oby.20811
|View full text |Cite
|
Sign up to set email alerts
|

Variations in body weight, food intake and body composition after long-term high-fat diet feeding in C57BL/6J mice

Abstract: Objective To investigate the variations in body weight, food intake and body composition of both male and female C57BL/6J mice during a diet-induced obesity (DIO) model with high-fat diet (HFD) feeding. Design and Methods Mice were individually housed and fed ad libitum either a low-fat diet (LFD, 10% calories from fat; n=15 male, n=15 female) or high-fat diet (HFD, 45% calories from fat; n=277 male, n=278 female) from 8 to 43 weeks of age. Body weight, food intake and body composition were routinely measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
191
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(233 citation statements)
references
References 19 publications
40
191
2
Order By: Relevance
“…Mice fed the HF diet showed a significant increase in body weight; body fat composition; serum levels of triglycerides, nonesterified fatty acids, total and LDL cholesterol; and increased hepatic steatosis (Figure S1, Table S4). These results are in agreement with previous animal studies showing similar metabolic effects of HF diets [20, 22], which validates our dietary model.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Mice fed the HF diet showed a significant increase in body weight; body fat composition; serum levels of triglycerides, nonesterified fatty acids, total and LDL cholesterol; and increased hepatic steatosis (Figure S1, Table S4). These results are in agreement with previous animal studies showing similar metabolic effects of HF diets [20, 22], which validates our dietary model.…”
Section: Resultssupporting
confidence: 93%
“…A subset of livers was selected for RNA expression profiling, and a subset of pituitary glands was sent for histological evaluation. Because sex differences exist in the response of C57BL/6J mice to dietary models [20], we compared same-sex animals in experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…Further technological advancements will be needed to study live adult MCs post-sorting in these jet-in-air systems since we observed cell breakage that reduces viability. Furthermore, only male mice were sampled in this study due to the known substantial differences between males and females in growth curves post-weaning 48,49 . Future studies will need to explore if sex variants exist between MC growth and protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Suman et al observed increased obesity-related factors 12 months after 56-Fe radiation exposure in female C57BL/6J mice (Suman et al 2016). Studies have shown genetic-related (Carter et al 1997;Fearnside et al 2008) and sex-related (Hwang et al 2010;Yang et al 2014) differences in dietinduced body weight increases in various mouse strains. For example, male C57BL/6J mice are more susceptible to dietinduced overweight than females; it also progresses more slowly in females (Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown genetic-related (Carter et al 1997;Fearnside et al 2008) and sex-related (Hwang et al 2010;Yang et al 2014) differences in dietinduced body weight increases in various mouse strains. For example, male C57BL/6J mice are more susceptible to dietinduced overweight than females; it also progresses more slowly in females (Yang et al 2014). However, studies have shown that more women are obese than men (Kanter and Caballero 2012).…”
Section: Introductionmentioning
confidence: 99%